Stimulation of TRPA1 attenuates ischemia-induced cardiomyocyte cell death through an eNOS-mediated mechanism. Issue 1 (1st January 2019) - Andrei, Spencer R.; Ghosh, Monica; Sinharoy, Pritam; Damron, Derek S.
ABSTRACT: The functional expression of transient receptor potential cation channel of the ankyrin-1 subtype (TRPA1) has recently been identified in adult mouse cardiac tissue where stimulation of this ion channel leads to increases in adult mouse ventricular cardiomyocyte (CM) contractile function via a Ca 2+ -Calmodulin-dependent kinase (CaMKII) pathway. However, the extent to which TRPA1 induces nitric oxide (NO) production in CMs, and whether this signaling cascade mediates physiological or pathophysiological events in cardiac tissue remains elusive. Freshly isolated CMs from wild-type (WT) or TRPA1 knockout (TRPA1 -/- ) mouse hearts were treated with AITC (100 µM) and prepared for immunoblot, NO detection or ischemia protocols. Our findings demonstrate that TRPA1 stimulation with AITC results in phosphorylation of protein kinase B (Akt) and endothelial NOS (eNOS) concomitantly with NO production in a concentration- and time-dependent manner. Additionally, we found that TRPA1 induced increases in CM [Ca 2+ ]i and contractility occur independently of Akt and eNOS activation mechanisms. Further analysis revealed that the presence and activation of TRPA1 promotes CM survival and viability following ischemic insult via a mechanism partially dependent upon eNOS. Therefore, activation of the TRPA1/Akt/eNOS pathway attenuates ischemia-induced CM cell death.